Manajemen Strategi Dakwah di Era Kontemporer - H. Sofyan Hadi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2019)
The complexity of life is increasing in a sophisticated way. The evolution of human civilization from primitive conditions to being completely technological is a reality that cannot be denied. This is due to talking about a civilization certainly will not be separated from people's lives as a continuous activity. The development of technology directs the activities of life to always look for opportunities behind the crevices of creative thinking piles of each individual. Therefore, the chance of getting these opportunities is getting smaller. Especially if we focus our study in the context of da'wah (an invitation to Islam) which is a noble activity to invite people on the right path according to the religious guidance that God commands through the great prophet Muhammad PBUH and its truth is highly recognized. Therefore, this paper discussed about management strategies that are correlated with Da'wah because preaching with a noble vision will not be successful without good management and strategy.